Water and Sanitation Practices among the Migrant Slum Dwellers: A Sociological Study in Sylhet City - KAMAL, MOHAMMAD MOSTUFA (Advances in Social Sciences Research Journal, 2018)
Water and sanitation are very important for human life. In Bangladesh, the water and sanitation condition is not satisfactory, especially for slum dwellers. Majority of slum dwellers are poor migrants. This study tries to explore the water and sanitation practices of slum dwellers. The data of this research has been collected through In-depth interviews observation and Case studies etc. This study shows that most of the slum dwellers are very poor and illiterate. They have not no enough money to maintain their family. They are unaware of hygiene and sanitation. Most of them drink the supply water without boiling it. For this reason, they suffer from various diseases.